Caribbean Remittance Forum on Enhancing the Efficiency and Integrity of Remittance Transfers through Effective Regulatory and Supervisory Systems in the Caribbean - World Bank; Government of Canada (World Bank, Washington, DC, 2013)
This regional forum aims at sharing knowledge and generating policy dialogue among relevant remittance stakeholders to enhance the efficiency and integrity of the migration and remittance transfer process, through effective regulatory and supervisory systems in the Caribbean region. It allows multiple countries to share their experiences, identify common challenges, learn from each others' experiences and discuss potential solutions to these challenges. The forum will also provide opportunities for networking. The past discussions on remittances and migration in the Caribbean focused largely on issues related to the Caribbean Diaspora, such as the brain-drain syndrome, the macroeconomic impact of remittances, the use of remittances for investment purposes, overall remittance patterns and trends, and remittance data collection and monitoring issues. In recent years, however, the regulatory framework for Remittance Service Providers (RSPs) has been introduced or substantially enhanced in many countries, triggered by the need to address money laundering and terrorist financing concerns. This forum focuses the discussion on regulatory practices within and outside the Caribbean region with a view to share best practices and lessons learned.